2019
DOI: 10.3389/fnins.2019.00429
|View full text |Cite
|
Sign up to set email alerts
|

Effects of FGF2/FGFR1 Pathway on Expression of A1 Astrocytes After Infrasound Exposure

Abstract: Two types of reactive astrocytes, A1 and A2 astrocytes, are induced following neuroinflammation and ischemia. In this study, we evaluated the effects of the fibroblast growth factor (FGF)2/FGF receptor (FGFR)1 pathway on A1 and A2 astrocytes in the rat hippocampus using double-labeling immunofluorescence following infrasound exposure. A1 astrocytes were induced in the CA1 region of the hippocampus after exposure to infrasound for 3 days. The number of microglial cells was also increased, and we investigated if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…Although CXCR7 small interfering RNA or CXCR7 knockout animals can be considered to further confirm the function of CXCR7 as the downstream mediator in microglia, our results suggest that there may be other mechanisms involved in the induction of A1 astrocytes by microglia. For example, Zou et al demonstrated that the inhibition of the fibroblast growth factor 2/fibroblast growth factor 2, receptor 1 (FGF2/FGFR1) pathway resulted in an increase in A1 astrocytes after infrasound damage [58]. Therefore, there are other receptors and signaling pathways related to the unbalanced polarization of astrocytes toward the A1 phenotype in the development of CPSP, which requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…Although CXCR7 small interfering RNA or CXCR7 knockout animals can be considered to further confirm the function of CXCR7 as the downstream mediator in microglia, our results suggest that there may be other mechanisms involved in the induction of A1 astrocytes by microglia. For example, Zou et al demonstrated that the inhibition of the fibroblast growth factor 2/fibroblast growth factor 2, receptor 1 (FGF2/FGFR1) pathway resulted in an increase in A1 astrocytes after infrasound damage [58]. Therefore, there are other receptors and signaling pathways related to the unbalanced polarization of astrocytes toward the A1 phenotype in the development of CPSP, which requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…Iba-1 is a marker of reactive microglia (Imai and Kohsaka 2002). Microglial activation presumably involves the FGF2/ FGFR1 (fibroblast growth factor and receptor) pathway as can be seen when this pathway is blocked (Zou et al 2019). Microglia play an important role in modulating inflammation, and especially the polarized (ARM) microglia contribute to a more regenerative environment.…”
Section: Iba-1mentioning
confidence: 99%
“…We demonstrate that NHP reactive astrocytes are not aligned with either the A1 or A2 astrocyte profiles previously identified in rodents 5,6 . Indeed, while a minor subset of A1 markers (MX1, SerpinG1, and FKBP5) were enriched in several reactive astrocyte subtypes, most A1 markers analysed were not, including crucial indicators such as PSMB8, SRGN and especially complement component C3, previously described as a surrogate marker of A1 astrocytes 5,[46][47][48] . Instead, all reactive astrocyte subtypes upregulated a combination of A1 and A2 markers.…”
Section: Discussionmentioning
confidence: 92%